A Bauer-Hausdorff Matrix Inequality - Zizong Yan; Shanhe Wu (Abstract and Applied Analysis)
We present a biorthogonal process for two subspaces of ℂn. Applying this process, we derive a matrix inequality, which generalizes the Bauer-Hausdorff inequality for vectors and includes the Wang-IP inequality for matrices. Meanwhile, we obtain its equivalent matrix inequality.